Degradable ceramic body mud and manufacturing method thereof
By mixing composite stone with grinding and ball milling, and stirring and calcining with specific components, degradable ceramic sludge is produced, which solves the problem that it is difficult to take into account high hardness, strength and degradability in the production process of ceramic plating, and achieves high performance and low cost production of ceramic products.
Patent Information
- Application Number
- CN202411789005.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-06
AI Technical Summary
It is difficult for existing ceramic blanks to take into account high hardness, strength and degradability during the production process, and the production costs are relatively high.
By grinding calcined talc, wollastonite, mica and yttrium stabilized zirconia into composite stone, and ball milling with components such as stearic acid, carboxymethyl chitosan solution, polyhydroxycitronellal and aluminum-zirconium coupling agent, the slurry is added after forming the slurry, and then the binder and deionized water are added. After pressing, molding, vacuum drying and calcining, a degradable ceramic mud is finally produced.
It achieves high hardness and strength of ceramic products, and has good degradability and mechanical properties, has a wide range of raw materials, low production costs, and environmentally friendly processes.
Smart Images

Figure BDA0005174851760000061 
Figure BDA0005174851760000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramics and relates to a degradable ceramic clay and a manufacturing method thereof. Background Art
[0002] The blanks for ceramic containers are usually made of a mixture of clay, quartz, feldspar and other raw materials in a specific proportion, and are made into container shapes through molding processes (such as throwing, slip injection, etc.). After drying and bisque firing, the blanks become hard and strong ceramic embryos, and finally glaze and high-temperature firing are performed to form decorative and practical ceramic containers.
[0003] The patent document with publication number CN103771829A discloses a ceramic product, which is made of the following raw materials in parts by weight: 20-23 parts of quartz sand, 30-34 parts of potassium feldspar, 10-12 parts of hard kaolin, 50-55 parts of clay, 23-25 parts of bentonite, 5-10 parts of wollastonite powder, 3-4 parts of zinc oxide, 4-5 parts of magnesium oxide, 20-24 parts of loess powder, and 5-6 parts of additives. The additives are made of the following raw materials in parts by weight: 2-3 parts of brown corundum powder, 5-6 parts of sodium tripolyphosphate, 4-5 parts of jade powder, 1-2 parts of silane coupling agent KH-550, 4-5 parts of silicon carbide powder, and 8-10 parts of aluminum hydroxide; the preparation method is to mix the materials, grind and disperse them evenly, and obtain the product. The advantage of this patent document is that hard kaolin, bentonite, wollastonite powder and other raw materials are added to the raw material formula, which enhances the strength and toughness of the embryo, increases the plasticity, and promotes the bonding of the raw materials, so that the prepared ceramic products have good strength and bending resistance, and a fine and dense texture. Summary of the invention
[0004] The object of the present invention is to provide a degradable ceramic clay and a method for producing the same. The ceramic clay of the present invention is suitable for producing ceramic products. The products have high hardness and strength, good degradability and mechanical properties, a wide range of raw materials, and low production costs.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing a degradable ceramic clay comprises the following steps:
[0007] S1, grinding and crushing calcined talc, wollastonite, phlogopite and yttria-stabilized zirconia, and sieving to obtain a composite stone;
[0008] S2, the composite stone, stearic acid and carboxymethyl chitosan solution are ball-milled and mixed, polyhydroxycitronellal and anhydrous ethanol are added under a nitrogen atmosphere, and then the mixture is stirred at a constant temperature, the solvent is filtered off and dried, and then isobutyl alcohol and aluminum zirconium coupling agent are added, and the mixture is stirred continuously, filtered, washed and vacuum dried to obtain a slurry;
[0009] S3, adding a binder and deionized water to the slurry, stirring, standing, pressing into shape, vacuum drying and then calcining to obtain.
[0010] As a preferred technical solution of the present invention, in step S1, the mass ratio of the calcined talc, wollastonite, phlogopite and yttria-stabilized zirconia is 10-12:7-8:3-5:1.2-1.5; and the screening is through a 200-mesh sieve.
[0011] As a preferred technical solution of the present invention, in step S2, the ball milling mixing time is 1.5-2.0h; the constant temperature stirring is stirring at 50-60°C for 4-5h; and the continued stirring is stirring at 500-600r / min for 3-4h.
[0012] As a preferred technical solution of the present invention, in step S2, the washing is washing three times with anhydrous ethanol; and the vacuum drying is drying at a temperature of 80° C. to constant weight.
[0013] As a preferred technical solution of the present invention, in step S2, the mass ratio of the composite stone, stearic acid, carboxymethyl chitosan solution, polyhydroxycitronellal, anhydrous ethanol, isobutanol and aluminum zirconium coupling agent is 100-110:12-14:160-170:3.2-3.6:40-50:130-140:2.8-3.0; the aluminum zirconium coupling agent is aluminum zirconium coupling agent TL-3A; the preparation of the polyhydroxycitronellal includes the following steps: after mixing 30 parts by weight of isobutanol and 2 parts by weight of citronellal, 1.5 parts by weight of thioglycerol and 0.08 parts by weight of photoinitiator 1173 are added, and after ultraviolet irradiation at a wavelength of 365nm for 6 hours, the solvent is removed by rotary evaporation to obtain the product.
[0014] As a preferred technical solution of the present invention, in step S2, the carboxymethyl chitosan solution is prepared by mixing carboxymethyl chitosan, acetic acid and deionized water in a mass ratio of 2.0-2.2:0.3-0.4:80-85.
[0015] As a preferred technical solution of the present invention, in step S3, the stirring time is 2-3 hours; the standing time is 24 hours at room temperature; and the vacuum drying is vacuum drying at 85°C to constant weight.
[0016] As a preferred technical solution of the present invention, in step S3, the calcination is performed at a temperature of 1080-1200° C. for 5-6 hours.
[0017] As a preferred technical solution of the present invention, in step S3, the mass ratio of the slurry, the binder and the deionized water is 90-100:3.8-4.3:90-100; and the binder is polyvinyl alcohol.
[0018] The invention discloses a degradable ceramic clay prepared by the preparation method.
[0019] Beneficial effects of the present invention:
[0020] (1) The ceramic clay of the present invention is suitable for producing ceramic products, the products have high hardness and strength, good degradability and mechanical properties, a wide range of raw materials, and low production costs.
[0021] (2) The present invention uses polyvinyl alcohol as a green binder, which has excellent bonding properties that enhance the molding efficiency of the mud and is harmless to the environment. This process greatly enhances the mechanical strength, density and crack resistance of the ceramic green mud, while also improving its environmental protection properties.
[0022] (3) Polyhydroxycitronellal and carboxymethyl chitosan strengthen the modification of the stone surface and its uniform dispersion, thereby improving the microstructure of the material. The addition of environmentally friendly dispersants and binders reduces environmental pollution and achieves a dual improvement in performance and green ecology. DETAILED DESCRIPTION
[0023] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0024] Example 1
[0025] A method for preparing a degradable ceramic clay comprises the following steps:
[0026] S1, grinding and crushing calcined talc, wollastonite, phlogopite and yttria-stabilized zirconia, and sieving to obtain a composite stone; the mass ratio of the calcined talc, wollastonite, phlogopite and yttria-stabilized zirconia is 10:7:3:1.2; the sieving is through a 200-mesh sieve;
[0027] S2, the composite stone, stearic acid and carboxymethyl chitosan solution are ball-milled and mixed, polyhydroxycitronellal and anhydrous ethanol are added under nitrogen atmosphere, and constant temperature stirring is performed, the solvent is filtered off and dried, isobutanol and aluminum zirconium coupling agent are added, and stirring is continued, filtering, washing, and vacuum drying are performed to obtain a slurry; the ball milling mixing time is 1.5h; the constant temperature stirring is stirring at 50°C for 4h; the continued stirring is stirring at a speed of 500r / min for 3h; the washing is washing three times with anhydrous ethanol; the vacuum drying is drying at 80°C to constant weight; the mass ratio of the composite stone, stearic acid, carboxymethyl chitosan solution, polyhydroxycitronellal, anhydrous ethanol, isobutanol and aluminum zirconium coupling agent is 100:12:160:3.2:40:130:2.8; the carboxymethyl chitosan solution is prepared by mixing carboxymethyl chitosan, acetic acid and deionized water in a mass ratio of 2.0:0.3:80;
[0028] S3. Add a binder and deionized water to the slurry, stir, let stand, press into shape, vacuum dry and then calcine to obtain; the stirring time is 2 hours; the standing is 24 hours at room temperature; the vacuum drying is vacuum drying at 85°C to constant weight; the calcination is calcination at 1080°C for 5 hours; the binder is polyvinyl alcohol; the mass ratio of the slurry, the binder and the deionized water is 90:3.8:90.
[0029] Example 2
[0030] A method for preparing a degradable ceramic clay comprises the following steps:
[0031] S1, grinding and crushing calcined talc, wollastonite, phlogopite and yttria-stabilized zirconia, and sieving to obtain a composite stone; the mass ratio of the calcined talc, wollastonite, phlogopite and yttria-stabilized zirconia is 11:7.5:4:1.4; the sieving is through a 200-mesh sieve;
[0032] S2, the composite stone, stearic acid and carboxymethyl chitosan solution are ball-milled and mixed, polyhydroxycitronellal and anhydrous ethanol are added under nitrogen atmosphere, and constant temperature stirring is performed, the solvent is filtered off and dried, isobutanol and aluminum zirconium coupling agent are added, and stirring is continued, filtering, washing, and vacuum drying are performed to obtain a slurry; the ball milling mixing time is 1.8h; the constant temperature stirring is stirring at 55°C for 4.5h; the continued stirring is stirring at a speed of 550r / min for 3.5h; the washing is washing three times with anhydrous ethanol; the vacuum drying is drying at 80°C to constant weight; the mass ratio of the composite stone, stearic acid, carboxymethyl chitosan solution, polyhydroxycitronellal, anhydrous ethanol, isobutanol and aluminum zirconium coupling agent is 105:13:165:3.4:45:135:2.9; the carboxymethyl chitosan solution is prepared by mixing carboxymethyl chitosan, acetic acid and deionized water in a mass ratio of 2.1:0.35:82;
[0033] S3. Add a binder and deionized water to the slurry, stir, let stand, press into shape, vacuum dry and then calcine to obtain; the stirring time is 2.5 hours; the standing is 24 hours at room temperature; the vacuum drying is vacuum drying at 85°C to constant weight; the calcination is calcination at 1140°C for 5.5 hours; the binder is polyvinyl alcohol; the mass ratio of the slurry, binder and deionized water is 95:4:95.
[0034] Example 3
[0035] A method for preparing a degradable ceramic clay comprises the following steps:
[0036] S1, grinding and crushing calcined talc, wollastonite, phlogopite and yttria-stabilized zirconia, and sieving to obtain a composite stone; the mass ratio of the calcined talc, wollastonite, phlogopite and yttria-stabilized zirconia is 12:8:5:1.5; the sieving is through a 200-mesh sieve;
[0037] S2, the composite stone, stearic acid and carboxymethyl chitosan solution are ball-milled and mixed, polyhydroxycitronellal and anhydrous ethanol are added under nitrogen atmosphere, and constant temperature stirring is performed, the solvent is filtered off and dried, isobutanol and aluminum zirconium coupling agent are added, and stirring is continued, filtering, washing, and vacuum drying are performed to obtain a slurry; the ball milling mixing time is 2.0h; the constant temperature stirring is stirring at 60°C for 5h; the continued stirring is stirring at 600r / min for 4h; the washing is washing three times with anhydrous ethanol; the vacuum drying is drying at 80°C to constant weight; the mass ratio of the composite stone, stearic acid, carboxymethyl chitosan solution, polyhydroxycitronellal, anhydrous ethanol, isobutanol and aluminum zirconium coupling agent is 110:14:170:3.6:50:140:3.0; the carboxymethyl chitosan solution is prepared by mixing carboxymethyl chitosan, acetic acid and deionized water in a mass ratio of 2.2:0.4:85;
[0038] S3. Add a binder and deionized water to the slurry, stir, let stand, press into shape, vacuum dry and then calcine to obtain; the stirring time is 3 hours; the standing is 24 hours at room temperature; the vacuum drying is vacuum drying at 85°C to constant weight; the calcination is calcination at 1200°C for 6 hours; the binder is polyvinyl alcohol; the mass ratio of the slurry, the binder and the deionized water is 100:4.3:100.
[0039] Comparative Example 1
[0040] Compared with Example 3, Comparative Example 1 is different in that carboxymethyl chitosan is not used, and the remaining components, preparation steps and parameters are the same.
[0041] Comparative Example 2
[0042] Compared with Example 3, the difference in Comparative Example 2 is that citronellal replaces polyhydroxycitronellal, and the other components, preparation steps and parameters are the same.
[0043] Comparative Example 3
[0044] Compared with Example 3, Comparative Example 3 is different in that polyhydroxycitronellal is not used, and the other components, preparation steps and parameters are the same.
[0045] Comparative Example 4
[0046] Compared with Example 3, Comparative Example 4 is different in that an aluminate coupling agent DL-411D is used instead of an aluminum zirconium coupling agent, and the other components, preparation steps and parameters are the same.
[0047] Comparative Example 5
[0048] Compared with Example 3, the difference in Comparative Example 5 is that tetra-n-propyl zirconate replaces the aluminum zirconium coupling agent, and the other components, preparation steps and parameters are the same.
[0049] Comparative Example 6
[0050] Compared with Example 3, Comparative Example 6 is different in that no aluminum zirconium coupling agent is used, and the remaining components, preparation steps and parameters are the same.
[0051] The ceramic green clay obtained in Examples 1-3 and Comparative Examples 1-6 were respectively tested for flexural strength using a HYK-DPK digital display electric green clay flexural tester. The test results are shown in Table 1.
[0052] Table 1
[0053]
[0054]
[0055] From the test results in Table 1, it can be seen that compared with Comparative Examples 1-6, the ceramic clay prepared in Examples 1-3 of the present invention has excellent flexural strength.
[0056] In the preparation process of ceramic green mud, carboxymethyl chitosan, polyhydroxycitronellal and polyvinyl alcohol are added, and Schiff base structure and multiple hydroxyl groups are introduced at the same time, which can form a network structure in the ceramic green mud, improve its plasticity and toughness, improve the density of ceramic green mud, enhance the bonding force between particles, and optimize the microstructure. This helps to reduce the formation of cracks during the drying process, and can significantly affect the performance of the final ceramic product during the calcination process. The Schiff base structure has good thermal stability. At high temperatures, they can form a stable skeleton structure, which helps to maintain the structural integrity of the ceramic material and prevent softening or deformation at high temperatures; the Schiff base structure can promote chemical bonding between ceramic particles, increase the bonding strength inside the material by forming covalent bonds or other strong interaction forces, and thus improve the overall mechanical properties; polyhydroxycitronellal contains multiple hydroxyl groups to promote the bonding strength between the slurry and the binder, so that it reacts with the active sites on the ceramic surface at high temperatures, promotes the formation of liquid phase during sintering, accelerates the speed of particle rearrangement and pore removal, and improves the density of ceramic green mud.
[0057] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any indirect modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing degradable ceramic clay, characterized in that: The following steps are involved: S1, grinding and crushing calcined talc, wollastonite, phlogopite and yttria-stabilized zirconia, and sieving to obtain a composite stone; S2, the composite stone, stearic acid and carboxymethyl chitosan solution are ball-milled and mixed, polyhydroxycitronellal and anhydrous ethanol are added under a nitrogen atmosphere, and then the mixture is stirred at a constant temperature, the solvent is filtered off and dried, and then isobutyl alcohol and aluminum zirconium coupling agent are added, and the mixture is stirred continuously, filtered, washed and vacuum dried to obtain a slurry; S3, adding a binder and deionized water to the slurry, stirring, standing, pressing into shape, vacuum drying and then calcining to obtain.
2. The method for preparing a degradable ceramic clay according to claim 1, characterized in that: In step S1, the mass ratio of the calcined talc, wollastonite, phlogopite and yttria-stabilized zirconia is 10-12:7-8:3-5:1.2-1.5; and the sieving is through a 200-mesh sieve.
3. The method for preparing a degradable ceramic clay according to claim 1, characterized in that: In step S2, the ball milling mixing time is 1.5-2.0 hours; the constant temperature stirring is stirring at a temperature of 50-60° C. for 4-5 hours; and the continued stirring is stirring at a speed of 500-600 r / min for 3-4 hours.
4. The method for preparing a degradable ceramic clay according to claim 1, characterized in that: In step S2, the washing is performed by washing three times with anhydrous ethanol; and the vacuum drying is performed at a temperature of 80° C. to a constant weight.
5. The method for preparing a degradable ceramic clay according to claim 1, characterized in that: In step S2, the mass ratio of the composite stone, stearic acid, carboxymethyl chitosan solution, polyhydroxycitronellal, anhydrous ethanol, isobutanol and aluminum zirconium coupling agent is 100-110:12-14:160-170:3.2-3.6:40-50:130-140:2.8-3.0; the carboxymethyl chitosan solution is prepared by mixing carboxymethyl chitosan, acetic acid and deionized water in a mass ratio of 2.0-2.2:0.3-0.4:80-85.
6. The method for preparing a degradable ceramic clay according to claim 1, characterized in that: The preparation of the polyhydroxycitronellal comprises the following steps: 30 parts by weight of isobutyl alcohol and 2 parts by weight of citronellal are mixed, 1.5 parts by weight of thioglycerol and 0.08 parts by weight of photoinitiator 1173 are added, and after irradiating with ultraviolet light at a wavelength of 365 nm for 6 hours, the solvent is removed by rotary evaporation to obtain the polyhydroxycitronellal.
7. The method for preparing a degradable ceramic clay according to claim 1, characterized in that: In step S3, the stirring time is 2-3 hours; the standing time is 24 hours at room temperature; and the vacuum drying is vacuum drying at 85° C. to constant weight.
8. The method for preparing a degradable ceramic clay according to claim 1, characterized in that: In step S3, the calcination is carried out at a temperature of 1080-1200° C. for 5-6 hours.
9. The method for preparing a degradable ceramic clay according to claim 1, characterized in that: In step S3, the mass ratio of the slurry, the binder and the deionized water is 90-100:3.8-4.3:90-100; the binder is polyvinyl alcohol.
10. A degradable ceramic clay prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
High-plasticity toughened daily use ceramic product
CN103771829A
Fabric treatment compositions comprising targeted benefit agents
CN103068958A
Structure type antibacterial moisture curing polyurethane hot melt adhesive and preparation method thereof
CN110194944A
Preparation and application methods of high-whiteness, high-transmittance and high-plasticity ceramic body mud
CN113480298A
Cited By
Preparation method of high-strength sintered tile
CN120574031A